ANALISIS HUBUNGAN KADAR GULA DARAH PUASA DENGAN KADAR KOLESTEROL HIGH DENSITY LIPOPROTEIN (HDL) PADA PASIEN DIABETES MELLITUS TIPE 2 DI RSUP SANGLAH - nyoman jirna (Jurusan Analisis Kesehatan, Poltekkes Kemenkes Denpasar, 2016)
Abstract Diabetes mellitus (DM) is a group of metabolic diseases with characteristic hyperglycemia that happen by abnormal secretions of insulin, insulin action, or both. The condition of insulin resistance in DM type 2 cause abnormal lipid metabolism that indicated by increase or decrease levels of lipid fraction in plasma, include increase levels of Very Low Density Lipoprotein (VLDL) or triglycerides, decrease levels of High Density Lipoprotein (HDL), and formed small dense Low Density Lipoprotein (LDL). The purpose of this study is to determine the relationship between the fasting blood sugar levels with HDL cholesterol levels in patients with DM type 2. The method use an analytical study with cross sectional design. Sampling examined as many as 35 samples by purposive sampling. The relationship between fasting blood sugar levels with HDL cholesterol levels is analyzed by Pearson Product Moment Correlation test. Based on the result concluded that there is a relationship between fasting blood sugar levels with HDL cholesterol levels in patients with DM type 2 in RSUP Sanglah with significant value sig=0,030 (sig